ASEAN Regional Forum 2017 : Annual security outlook (Philippines: Office of ASEAN Affairs, 2017)
The ASEAN Regional Forum Annual Security Outlook (ARF ASO) 2017 features submission from 20 ASEAN Regional Forum (ARF) participants in which they shared their perspectives on the current state of the regional security environment and presented their respective efforts at the national, regional and global levels - including contribution to the ARF process - in addressing various security challenges .
Foreword -- Executive Summary -- Australia -- Brunei -- Cambodia -- Canada -- China -- Democratic People's Republic of Korea -- European Union -- India -- Indonesia -- Japan -- Malaysia -- Myanmar -- New Zealand -- The Philippines -- Republic of Korea -- The Russian Federation -- Singapore -- Thailand -- The United States of America -- Viet Nam .
Keywords: ASEAN FORUM; FORUM 2017; ASEAN FORUM -- PHILIPPINES